Desktop Based Database System Learning Media Application Design with MS Visual Basic Net 8.0 - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Ami, Hutri; Tarigan, Gabriel Frandika; Perdana, Nugraha Aditama Putra (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
In the modern era, information technology in education is becoming increasingly important. This is why creating a desktop-based database learning media application using Microsoft Visual Basic Net 8.0 is a strategic step to improve the efficiency and quality of education. Additional application programs that can be used to design and create learning media, particularly in math education, are the subject of this article. Visual Basic, a programming language that is also taught in many college degree programs, is one such application program that can replace teachers who need to provide exercises and examples.